Problem-Based Learning Implementation for Students’ Speaking Achievement - Yunda Lestari; Rudi Hartono; Issy Yuliasri; Hendi Pratama (Universitas Negeri Semarang, 2023)
This article aims at providing a summary of various other studies that investigate how implementing Problem-Based Learning Approach can help students improve their speaking achievement. The method of study that was utilized was called a literature review, and it began with the process of seeking for research questions, searching for literature, evaluating data, and then analyzing it. After doing a search for research publications, the researcher came across five articles, then analyzed and contrasted with one another. This literature analysis came to the conclusion that the findings of the study showed that students not only improved their speaking performance after being treated through PBL activities, but also exhibited a more favorable behavioral, cognitive, and affective attitude toward English Language Learning (ELL). This was observed in the context of the study's findings that students demonstrated better speaking performance after being treated through PBL activities. PBL as a learning model for English was appropriate to make students fluent in communicating in English. Besides, PBL can also make students more active, confident, and enjoyable. As a result, problem-based learning may be one of the appropriate teaching approaches to increase students' capacity to speak English. This is because problem-based learning provides students with the opportunity to relate themselves to real-life challenges that require real-life answers.